Andy Gump Fracture of the Mandible in a Pediatric Patient - Mulinari-Santos, Gabriel [UNESP]; Lima, Valthierre Nunes [UNESP]; Palacio-Muñoz, Xiomara Mónica Johanna [UNESP]; De Oliva, André Hergesel [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Polo, Tárik Ocon Braga [UNESP]; Souza, Francisley Ávila [UNESP]; Garcia-Júnior, Idelmo Rangel [UNESP]; Faverani, Leonardo Perez [UNESP] (My University, 2017)
The mandibular fractures in pediatric patients are rare, and they can need a fast and safe treatment. We present a case of a pediatric patient with Andy Gump fracture, resulting in a retrognathic mandible, distress to breathe, and functional discomfort to the patient caused by a cycling accident. The treatment was successful with the fast release of airway path and use of titanium plates to fix the fracture.
Keywords: Facial trauma; mandible fracture; pediatric